Assembly Supervisory Role Of Regional Efforts In Order To Guidance And Supervision Of Notary In The District Of Cirebon - Fella Mudiana Putri; Farhan Munirus Su'aidi; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to: 1) analyze the implementation of MPD Cirebon role in the Framework Guidance and Control of Notaries. 2) analyze any efforts undertaken 3) analyze Barriers and Solutions MPD Cirebon in order to guidance and supervision of a Notary. This research is empirical. The method is empirical juridical approach. Specifications required in this research is descriptive. In this study consisted of data sources: primary data obtained by researchers through interviews and field research object Supervisory Council of Blood (MPD) in Cirebon, and secondary data obtained through literature.Based on data analysis concluded 1) implementation of the supervision and oversight of the Regional Supervisory Council (MPD) Cirebon based on regulation Minister of Law and Human Rights of the Republic of Indonesia Number M.39.PW.07 2004, of carrying out the authority, as referred to in Article 13 paragraph (2), Article 14, Article 15, Article 16 and Article 17 and Article 70 and Article 71 UUJN. 2) Some of the efforts to be undertaken by the Assembly Regional Supervising Notary Cirebon in order to guidance and supervision of Notaries are: a) Implement supervision preventive and curative namely the prevention of the occurrence of malfeasance Notary and to provide guidance to the Notary itself, b) do socializations to the parties related to the Notary profession. 3) Factors to be barriers: 1) Notary less able to manage time between activities Notary with the time of inspection. 2) Notary also encountered less tidy in making a Notary Protocol. As for the solution is 1) Should the Notary make a schedule for the activities to be performed 2) Notary further explore and relearn the theories about the creation of Notary Protocol. 3) The area should be routinely Supervisory Council to follow up on the findings of the Regional Supervisory Council of Notaries.Keywords: MPD; Development and Supervision; Sanctions.